Neuromagnetic Assessment of Pathophysiologic Brain Activity Induced by Minor Head Trauma - Lewine, Jeffrey David; Davis, John T.; Sloan, John Henry; Kodituwakku, P. W.; Orrison Jr, William W. (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Patients with mild traumatic brain injury (TBI) often show significant neuropsychological dysfunction despite the absence of abnormalities on traditional neuroradiologic examinations or EEG. Our objective was to determine if magnetic source imaging (MSI), using a combination of MR imaging and magnetoencephalography (MEG), is more sensitive than EEG and MR imaging in providing objective evidence of minor brain injury.METHODS: Four subject groups were evaluated with MR, MSI, and EEG. Group A consisted of 20 neurologically normal control subjects without histories of head trauma. Group B consisted of 10 subjects with histories of mild head trauma but complete recovery. Group C consisted of 20 subjects with histories of mild head injury and persistent postconcussive symptoms. The 15 subjects included in group D underwent repeat examinations at an interval of 2 to 4 months.RESULTS: No MR abnormalities were seen in the normal control group or the asymptomatic group, but five (20%) of the patients with persistent postconcussive symptoms had abnormal MR findings. EEG was abnormal for one subject (5%) from the normal control group, one (10%) from the asymptomatic group, and five (20%) from the group with persistent postconcussive symptoms. MSI was abnormal for one subject (5%) from the normal control group, one (10%) from the asymptomatic group, and 13 (65%) from the group with persistent postconcussive symptoms. There was a direct correlation between symptom resolution and MSI findings for the symptomatic head trauma group.CONCLUSION: MSI indicated brain dysfunction in significantly more patients with postconcussive symptoms than either EEG or MR imaging (P < .01). The presence of excessive abnormal low-frequency magnetic activity provides objective evidence of brain injury in patients with postconcussive syndromes and correlates well with the degree of symptomatic recovery.